Effects of ZnO nanohexagons and nanorods on the fluorescence behavior of metallophthalocyanines. (8th January 2015) - D'Souza, Sarah; Moeno, Sharon; Nyokong, Tebello
Abstract : Graphical abstract: Fluorescence quantum yields of Pc complexes generally decrease in the presence of ZnO nanoparticles, fluorescence lifetimes of Pc complexes generally decreased in the presence of ZnO nanoparticles, with generally longer lifetimes for ZnO nanohexagons compared to ZnO nanorods. Abstract: This paper looks at the fluorescence behavior of zinc phthalocyanines: 2, (3), 9(10), 16(17), 23(24)-tetrakis-(mercaptoacetic acid phthalocyaninato) zinc(II) (ZnTMAAPc), 2, (3), 9(10), 16(17), 23(24)-tetrakis-(mercaptopropanoic acid phthalocyaninato) zinc(II) (ZnTMPAPc) and (OH)AlPcSmix (the latter contains a mixture of the di-, tri- and tetra-sulfonated derivatives with an average of three sulfonated groups per molecule) in the presence of ZnO nanoparticles. Fluorescence lifetimes of Pc complexes generally decreased in the presence of ZnO nanoparticles, with generally longer lifetimes for ZnO nanohexagons compared to ZnO nanorods.